PEMBINAAN PELAKU USAHA PARIWISATA OLEH DINAS PARIWISATA KEBUDAYAAN KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUMEDANG - Qori, Aghnia Amalia (LPPM UNSAP & FISIP UNSAP, 2025)
This research aims to identify how the Department of Tourism, Culture, Youth and Sports of Sumedang Regency conducts the development of tourism business actors. The research method used in this study is a qualitative method. Informants were selected using purposive sampling, consisting of the Head of the Tourism Division, the Expert Junior Staff of Tourism and Creative Economy, Staff of the same division, as well as the managers of Kampung Karuhun and Puteri River Inn tourist destinations. Data collection techniques involved literature studies and field studies through observation, interviews, documentation, and triangulation. Data validity was ensured through credibility, transferability, dependability, and confirmability tests. The data analysis techniques used include data collection, data reduction, data display, and verification. The results indicate that the development of tourism business actors by the department has not been optimal. It remains incidental, is not conducted regularly, and does not cover all tourism sectors. Additionally, no updated and continuous development guidelines are available.